Obesity contributes to the stealth peritoneal dissemination of ovarian cancer: a multi‐institutional retrospective cohort study. Issue 8 (18th July 2022) - Iyoshi, Shohei; Sumi, Asami; Yoshihara, Masato; Kitami, Kazuhisa; Mogi, Kazumasa; Uno, Kaname; Fujimoto, Hiroki; Miyamoto, Emiri; Tano, Sho; Yoshikawa, Nobuhisa; Emoto, Ryo; Matsui, Shigeyuki; et al.
Abstract: Objective: The clinical significance of a higher BMI on the prognosis of ovarian cancer remains controversial; therefore, a more detailed analysis is demanded. This study investigated the impact of BMI on peritoneum‐specific recurrence to clarify the involvement of adipose tissue in the proliferation of cancer cells at sites of peritoneal dissemination. Methods: Among 4, 730 patients with malignant ovarian tumors, 280 diagnosed with International Federation of Gynecology and Obstetrics (FIGO) stage IIB to IIIC epithelial ovarian cancer and who underwent complete resection in the primary surgery were included in the present study. Results: There were 42, 201, and 37 women in the low, normal, and high BMI groups, respectively. Peritoneum‐specific recurrence‐free survival and overall survival were both significantly shorter in patients with a high BMI than in those with a normal BMI ( p  = 0.028 and 0.018, respectively). No significant differences were observed in the distribution of sites of recurrence between these two groups. A multivariate analysis identified obesity as an independent prognostic factor in addition to pT3 tumor staging and positive ascites cytology. Conclusions: Patients with a high BMI had a significantly worse prognosis than those with a normal BMI, and peritoneal adipose tissue may have contributed to this difference.